Improving Reading Comprehension: Comparing the Effectiveness of Integrated KWL with Think Pair Share and the Original KWL Strategy - Sambuaga, Nur Azizah; Raja, Patuan; Sukirlan, Muhammad (Universitas PGRI Sumatera Barat, 2025)
AbstractThis study aimed to find out whether the integrated KWL (Know-Want-Learn) strategy with Think Pair Share improves students' reading comprehension better than the Original KWL Strategy. This research employed a quantitative method. The study was conducted with first-grade students at SMPN 14 Bandar Lampung. Two classes were used: an experimental class, which was taught using the integrated KWL and Think Pair Share strategy, and a control class, which was taught using the original KWL strategy. The results of the post-test showed that the control group had a mean score of 70.32, whereas the experimental group had a higher mean score of 79.35. The t-test results for the post-test indicated a Sig. (2-tailed) value was 0.003 (< 0.05), there is a statistically significant difference between the two groups after the treatment. The experimental group achieved better improvement in reading comprehension compared to the control group. These findings suggest that integrating the KWL strategy and Think Pair Share improves students' reading comprehension.